Use of gamification through the “Pass-Pass” game: an experience with General Biochemistry students (Research, Society and Development, 2022)
Biochemistry is a discipline present in several undergraduate courses. However, the literature points out that it is a discipline known to be difficult to understand and high failure rates. The objective of this work was to provide opportunities and evaluate students in the face of the experience of learning biochemistry through the use of gamification, leaving the usual process of teaching and learning and bringing different elements of competition, using a game like "Pass Repass". Among the applied questions about animal biochemistry before and after the game, most showed an increase in correct answers in the post game. This experience allowed us to conclude that the use of the pass-pass game as an active methodology, with university students in teaching and learning biochemistry, contributed positively to the improvement of post-game responses and a great motivation of students for the classes. Thus, the use of a “Pass Pass” game proved to be a contributory tool to be used in biochemistry, by instigating students to develop a taste for studying this discipline.